PEMENUHAN KEBUTUHAN JENDER DAN PENGURANGAN KEMISKINAN: STUDI KASUS DALAM PEMERINTAHAN DESA (Forum Ilmu Sosial, 2016)
Development in Indonesia continues to be improved to reduce the gap between rural and urban areas. Gapbetween villages and cities make the urbanization because the opening of full employment and public facilities in the city. These development must reflect justice for all people; things that need to be considered in rural development and gender mainstreaming.Opportunities and strength of development for villages in Indonesia reinforced by the Government Regulation Number 6/2014 on Village Governance. This article will discuss gender fulfillment needs in poverty reduction on a village. The research was conducted with qualitative research method with document analysis. This research chose Nglorog Village in Sragen as the subject due to the status of the village itself in Sragen which classified into the red area of poverty. Poverty in Sragen recorded 14,87%, higher than the poverty rate in the province of Central Java (13.58%) and higher than the average Indonesian poverty rate of 10.96%. The findings show that the quality of gender equality in the poverty reduction in Nglorog village planning regulation is in gender-neutral level and the poverty reduction program only focuses on the fulfillment of practical gender needs for women and marginal elements of the society.